Decreasing the amplitude of macroscopic quantum fluctuations in the case of transient SRS. (September 2020) - Didenko, N.V.; Konyashchenko, A.V.; Losev, L.L.
Abstract: It is shown experimentally that, under the conditions of transient stimulated Raman scattering, pumping by two successive orthogonally polarised laser pulses makes it possible to reduce the amplitude of macroscopic quantum energy fluctuations of a Stokes pulse by a factor of 4 in comparison with single-shot pumping. An energy dispersion of 0.9 % for the first Stokes component is obtained in hydrogen at a relative energy dispersion of ytterbium laser pulses of 0.4 %.